Analysis of Quality of Nuchal Translucency Measurements: Its Role in Prenatal Diagnosis. (30th April 2012) - Gabriel, Carmen Comas; Echevarria, M.; Rodríguez, I.; Serra, B.
Abstract : Objective . Quantitative analysis of the quality of nuchal translucency (NT) measurements. Methods . First-trimester combined screening for Down syndrome was performed to all pregnant women attended in our Department from October 2003 to November 2009. NT was measured according to the Fetal Medicine Foundation (FMF) criteria by 20 trained obstetricians. The performance of NT measurements was retrospectively analyzed with regard to several quality control standards. Accuracy according to experience, professional profile, crown rump length (CRL) values, and FMF certification was statistically tested. Results . A total of 14978 NT measurements were assessed. (1) The mean operator-specific median NT-MoM values was 0, 98. (2) Mean percentage of cases >95th and <5th centiles were 5, 0% and 4, 2%, respectively. (3) Logarithmic mean and SD of the NT MoM values were 0, 00 and 0, 13, respectively. (4) The DR for trisomy 21 at screening time was 90, 7% for a FPR of 6, 7% for standard screening strategy. (5) According to Cumulative SUM (CUSUM) figures, the performance was more acceptable in FMF-certified operators. Conclusion . Overall, quality standards show optimal NT measurements in our unit. Operator experience, a dedicated profile to fetal medicine, CRL over 60 mm, and FMF certification have a significant positive impact on the quality standards.